Originally Posted by

**alisheraz19** Hi Scott, thank you for your answers but I have to say I'm not quite following you came to that answer.... i mean.. no.. wait I understand how you came to it because but I don't understand why.. It's strange because in my book this is what it says about Limits at infinity:

here's the example.. Lim x--> infinity

(4x^2 + 5) / (2x^2+1)

||from the book|| For the preceding function there is an easier way to find the lim x--> infinity

For large values of x, in the numerator the term involving the greatest power of x, namely 4x^2, dominates the sum 4x^2+5, and the dominant term in the denominator 2x^2 +1 is 2x^2. Thus as x--> infinity, f(x) can be approximated by (4x^2)/ (2x^2)

thus: Lim x-->infinity 4x^2 / 2x^2 = lim x --> infinity 2 = 2

why can't this be applied to my question:

22. lim x--> ∞ 2x-4 / 3-2x

therefore 2x/2x = 1?